A Theory on the Impact of Copper and Micronutrients Against COVID-19 in Humans - Caitlin A. Connor DAOM PGDip AMP EHP-C (International Journal of Infection Prevention, 2021)
Copper (Cu) has a strong impact on the function of the immune system through several different pathways. These impacts include helping the function of monocytes, neutrophils, and macrophages, and enhancing Natural Killer cells’ activities. Cu also has a role in antimicrobial properties and inflammatory response. It is also important for IL-2 production and response, which is a component of adaptive immune cells. Additionally, Cu has multiple roles in both proliferation and differentiation of T cells and is involved in the production of antibodies. Cu deficiency can even lead to
Keywords: COVID-19